Synthesis and evaluation of tetrahydropyrazolopyridine inhibitors of anion exchange protein SLC26A4 (pendrin). Issue 16 (15th August 2019) - Zhu, Jie S.; Lu, Julia Y.; Tan, Joseph-Anthony; Rivera, Amber A.; Phuan, Puay-Wah; Shatskikh, Marina E.; Son, Jung-Ho; Haggie, Peter M.; Verkman, Alan S.; Kurth, Mark J.
Graphical abstract: Abstract: Pendrin is a transmembrane chloride/anion antiporter that is strongly upregulated in the airways in rhinoviral infection, asthma, cystic fibrosis and chronic rhinosinusitis. Based on its role in the regulation of airway surface liquid depth, pendrin inhibitors have potential indications for treatment of inflammatory airways diseases. Here, a completely regioselective route to tetrahydro-pyrazolopyridine pendrin inhibitors based on 1, 3-diketone and substituted hydrazine condensation was been developed. Structure-activity relationships at the tetrahydropyridyl nitrogen were investigated using a focused library, establishing the privileged nature of N -phenyl ureas and improving inhibitor potency by greater than 2-fold.